(FAN) Scholars and Superheroes: The Role and Status of Comics Fandom Research in Australian Media History. Issue 1 (May 2015) - Patrick, Kevin
Comic books, eagerly consumed by Australian readers and reviled with equal intensity by their detractors, became embroiled in post-war era debates about youth culture, censorship and Australian national identity. Yet there are few references to this remarkable publishing phenomenon in most histories of Australian print media, or in studies of Australian popular culture. This article demonstrates how the history of comic books in Australia has largely been recorded by fans and collectors who have undertaken the process of discovery, documentation and research – a task that, in any other field of print culture inquiry, would have been the preserve of academics. While acknowledging some of the problematic aspects of fan literature, the article argues that future research into the evolution of the comic-book medium within Australia must recognise, and engage with, this largely untapped body of 'fan scholarship' if we are to enrich our understanding of this neglected Australian media industry.